Efectos espaciales en la formación de precios en mercados minoristas de Gas Natural Vehicular (2015)
The gas distribution system for natural gas vehicles (NGV) in the Service Stations (EDS) in Colombia is highly concentrated, which gives the retail distributors market power. The pricing mechanism appears to approximate a Bertrand type of oligopolistic model, with a dominant firm setting the prices. The geographical location of the EDS generates strategies that influence price formation. In this research, a spatial contiguity matrix is designed, which includes socio-economic and distance characteristics, related to the EDS geographic location. We use a spatial panel model of Durbin type, which includes fundamental variables to explain the GNV price formation.